Muslim and science: contributions of Islamic universities to professional ethics (2010)
It is sad and paradoxical that Muslims who were once the precursors and torchbearers of the scientific knowledge that culminated in modern civilization, are today wallowing in a state of backwardness, ignorance and domination. Despite their global numerical strength of over one million people, only a few Muslim countries are currently making, any significant strides in shaping contemporary civilization and the state of the world. This paper examines how Islamic concept of khidfah (vice-gereney) can be employed to revive Islamic science so that it can sustain human and other creatures in a wholesome manner. It argues that teaching secular sciences according to Islamic principles, as is being done today at the international Islamic University Malaysia (IIUM) and Nigeria’s Crescent University, Abeokuta (CUA) will reverse such negative trends.